Thermal transport in monolayer InSe. (24th July 2017) - Nissimagoudar, Arun S; Ma, Jinlong; Chen, Yani; Li, Wu
Abstract: Two-dimensional InSe, a recently synthesized semiconductor having a moderate band gap, has gained attention due to its ultra high mobility and high photo-responsivity. In this work, we calculate the lattice thermal conductivity ( κ ) of monolayer InSe by solving the phonon Boltzmann transport equation (BTE) with first-principles calculated inter atomic force constants. κ of monolayer InSe is isotropic and found to be around 27.6 W m K − 1 at room temperature along the in-plane direction. The size dependence of κ shows the size effect can persist up to 20 μ m. Further, κ can be reduced to half by tuning the sample size to 300 nm. This low value suggests that κ might be a limiting factor for emerging nanoelectronic applications of monolayer InSe.